Shifting from Burden Sharing to Task Sharing: Advancing Community-Initiated Care in MHPSS for Refugee Resettlement - Hyojin Im (Social Sciences)
The complexities of refugee resettlement in the U.S. require comprehensive mental health and psychosocial support (MHPSS) strategies, yet significant gaps persist due to resettlement policies prioritizing short-term self-sufficiency over long-term mental health and well-being. This study explores the shift from traditional “burden sharing” to “task sharing” models that emphasize community-initiated care (CIC). Using a two-phase qualitative method, 27 refugee leaders and bilingual service providers from 14 refugee communities, including Afghan, Bhutanese, Burmese, Congolese, Somali, and Sudanese communities, across four states participated in focus groups or key informant interviews. Thematic analysis revealed that peer support models play a critical role as bridges between cultures, service sectors, and formal and informal networks. However, peer support remains insufficient without structural reform, as refugees face barriers such as lack of professional development and power imbalances with professionals while managing their own life challenges. This study emphasizes formalizing CIC models that empower refugees to lead the sharing process in collaborative care. Intersectoral collaboration and supportive policy frameworks are necessary to sustain peer support and build long-term leadership capacity. The findings highlight the need for a system-level shift to ensure equitable responsibility for care, fostering sustainable, community-driven MHPSS solutions in refugee resettlement.